2019
DOI: 10.1002/pds.4944
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of the Japanese Adverse Drug Event Report database (JADER)

Abstract: Introduction: The spontaneous adverse drug reaction (ADR) reporting system plays an important role in pharmacovigilance by providing information from clinical settings in the postmarketing environment. The Japanese Adverse Drug Event Report (JADER) database contains a portion of Japanese ADR reports, and no previous study has described the quality or characteristics of ADR reports in the JADER.Objective: The aim of this study was to identify the characteristics of the JADER database and to evaluate the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Given that signal detection is a hypothesis-generating study, future efforts to accumulate cases and confirm/refute hypotheses are desirable. In addition, information available on individual case safety reports is limited [ 23 ]. In particular, spontaneous reports do not include information on which term of pregnancy the drug was used, which is essential for assessing the causal relationship between drug exposure and pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Given that signal detection is a hypothesis-generating study, future efforts to accumulate cases and confirm/refute hypotheses are desirable. In addition, information available on individual case safety reports is limited [ 23 ]. In particular, spontaneous reports do not include information on which term of pregnancy the drug was used, which is essential for assessing the causal relationship between drug exposure and pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Completeness assessment tools include: the WHO's documentation grading scheme (8); vigiGrade (9), which was created to assess the quality of the information in VigiBase; the ATHE score (10); amongst other methods of calculating completeness scores (11)(12)(13). Here, we have analyzed the quality and characteristics of the JADER, using the WHO documentation grading scheme (14) and the vigiGrade (15). The WHO's documentation grading scheme, which was noted if essential elements (e.g., date of onset of ADR, duration of administration of suspected drugs, dose, and frequency of administration, rechallenge information) were given in the reports, could divide ADR reports into four grades.…”
Section: Introductionmentioning
confidence: 99%
“…Small sample sizes may increase these biases. Second, a previous study showed that the quality of reports differed depending on the facilities or occupations in the JADER database [ 34 ], and the quality of the reports was not evenly distributed. Third, although ROR is suggested to be less biased than the proportional reporting ratio, which is a ratio of reporting proportions, there are still various biases [ 35 ].…”
Section: Discussionmentioning
confidence: 99%